Effectiveness and safety of tolvaptan in liver cirrhosis patients with edema: Interim results of post‐marketing surveillance of tolvaptan in liver cirrhosis (START study). Issue 11 (6th February 2017) - Sakaida, Isao; Terai, Shuji; Kurosaki, Masayuki; Yasuda, Moriyoshi; Okada, Mitsuru; Bando, Kosuke; Fukuta, Yasuhiko
Abstract : Aim: Loop diuretics and spironolactone are used in patients with hepatic edema, but they are sometimes associated with insufficient responses as well as adverse events. Tolvaptan, a vasopressin type 2 receptor antagonist, was approved for hepatic edema in 2013. A large‐scale post‐marketing surveillance study has been carried out to evaluate the effectiveness and safety of tolvaptan in real‐world clinical settings. Methods: Patients with hepatic cirrhosis with insufficient response to conventional diuretics were enrolled. The observational period was up to 6 months. Changes in body weight and clinical symptoms were measured to evaluate effectiveness. The incidence of adverse drug reactions was summarized as a safety measure. Results: Of 970 patients enrolled, 463 were included in the safety analysis. Of this group, 340 were included in the effectiveness analysis. Decreases in body weight from baseline were −2.38 kg on day 7 and −3.52 kg on day 14. Ascites and bloated feeling was significantly improved within 14 days. The mean change in body weight depended on estimated glomerular filtration rate levels. The most frequently reported adverse drug reaction was thirst (6.9% of patients). Serum sodium level of ≥146 mEq/L was observed in 12 patients (2.7%). Conclusions: In the real‐world clinical setting, tolvaptan showed aquaretic effectiveness in patients with cirrhosis. The mean change in body weight depended on renal function. We recommend tolvaptan use for hepatic cirrhosis at a stage in which the renal function is maintained.